2021
DOI: 10.3390/ani12010087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Organic and Inorganic Sulfur on Laying Performance, Egg Quality, Ileal Morphology, and Antioxidant Capacity in Laying Hens

Abstract: The present study was conducted to investigate the comparative effects of organic and inorganic forms of sulfur, methyl sulfonyl methane (MSM) and sodium sulfate (SS), on laying performance, egg quality, ileal morphology, ileal volatile fatty acids, and antioxidant and stress markers in various biological samples in aged laying hens. A total of 144, 73-week-old Lohman Brown-Lite laying hens were randomly assigned to one of three experimental diets: basal diet (CONT), CONT + 0.2% MSM (MSM), and CONT + 0.3% SS (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Compared with sodium selenite, organic selenium integrated with bacteria or yeast improved the performance, egg quality, and selenium contents of tissues and eggs and increased beneficial caecal bacterial proliferation and butyric acid content in laying hens [26,27]. The addition of organic sulfur and inorganic sulfur to the diet was beneficial to the ileal morphology and antioxidant capacity of laying hens [28]. It can be seen from the above that the addition of organic acids and organic elements to feed can effectively improve the production of laying hens, which was confirmed again in this study, which showed that the addition of calcium lactate to feed improved the egg-production performance of laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with sodium selenite, organic selenium integrated with bacteria or yeast improved the performance, egg quality, and selenium contents of tissues and eggs and increased beneficial caecal bacterial proliferation and butyric acid content in laying hens [26,27]. The addition of organic sulfur and inorganic sulfur to the diet was beneficial to the ileal morphology and antioxidant capacity of laying hens [28]. It can be seen from the above that the addition of organic acids and organic elements to feed can effectively improve the production of laying hens, which was confirmed again in this study, which showed that the addition of calcium lactate to feed improved the egg-production performance of laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…Albumen weight was then calculated by subtracting yolk and dry eggshell weights from the initial whole egg weight. The separated yolks were pooled (3 yolks/replicate) and processed to determine the concentrations of corticosterone and malondialdhyde (MDA), as described elsewhere [23][24][25]. 4 14.49 Crude fat 4 4.01 Crude ash 4 14.84 Calcium 3 4.10 Sulfur 4 0.15 Available phosphorus 3 0.28 Total lysine 3 0.65 Total methionine 3 0.32 Total methionine + cysteine 3 0.60 Methyl sulfonyl methane 4 0.03…”
Section: Laying Performance Parameters and Egg Qualitymentioning
confidence: 99%
“…Histological sections (5 μm thick) were prepared using standard hematoxylin-eosin staining [24]. The mucosa was examined under a light microscope (Olympus BX43, Tokyo, Japan) and photographed using a digital camera (eXcope T500; DIXI Science, Daejeon, Korea).…”
Section: Ileal Morphologymentioning
confidence: 99%